Allometry, biomass, and productivity of deciduous oak forests in Xanthi, northern Greece - Kitikidou, Kyriaki; Milios, Elias; Radoglou, Kalliopi (Banko Janakari, 2024)
In this work, the data collected for the preparation of the management plans prepared by the Xanthi Forestry Service were used to estimate the biomass allometry and productivity of the deciduous oak forests. For the purpose of our study, the diameter at breast height (DBH), distribution of trees above breast height, and the wood stock amounts were analyzed. To estimate the aboveground biomass, three biomass models were tested. The DBH distribution clearly indicated that the majority of the stands were young, thus having a high net productivity. This fact suggests that, in order to get a fair estimate of biomass, a biomass expansion factor (BEF), used to convert volume to mass, should have a value close to the upper limit of the factor’s range, which is appropriate for young stands. The comparison of the three tested models proved that only one could be appropriate for use while the other two were completely unsuitable.